A dynamic view on work‐related perfectionism: Antecedents at work and implications for employee well‐being. Issue 4 (10th September 2022) - Mohr, Monique; Venz, Laura; Sonnentag, Sabine
Abstract: Little is known about the role of perfectionism in employees' daily work. Our study aimed to provide a fine‐grained view on perfectionism in work life by examining daily work‐related perfectionism in terms of perfectionistic strivings and concerns. Drawing on whole trait theory and the principle of trait activation, we investigated experienced time pressure and criticism at work as antecedents of daily work‐related perfectionism and in turn its implications for vigour and negative affect. In the course of two working weeks, 72 employees completed surveys three times per day, resulting in a total of 461 days of data. Multilevel path modelling showed that daily time pressure was positively related to both perfectionistic strivings and concerns, and that criticism was positively related to perfectionistic concerns. Daily work‐related perfectionistic strivings were positively indirectly related to vigour at bedtime via vigour at the end of the workday. Daily work‐related perfectionistic concerns were positively indirectly related to bedtime negative affect via end‐of‐workday negative affect. Our study shows that employees' daily experiences at work relate to within‐person fluctuations in work‐related perfectionism, which in turn matter for well‐being both at work and at home. We conclude that a dynamic view broadens the understanding of perfectionism at work.